1992
DOI: 10.1016/0378-1097(92)90347-q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two gene regions involved in the expression of the imipenem-specific, outer membrane porin protein OprD of Pseudomonas aeruginosa

Abstract: A Tn501 mutant of Pseudomonas aeruginosa resistant to imipenem and lacking the imipenem-specific outer membrane porin protein OprD was isolated. The mutation could be complemented to imipenem susceptibility and OprD-sufficiency by a cloned 6-kb EcoRI-PstI fragment of DNA from the region of chromosome of the wild-type strain surrounding the site of Tn501 insertion. However, this fragment did not contain the oprD structural gene as judged by its inability to hybridize with an oligonucleotide corresponding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…By contrast, the product of the gusC gene is an outer membrane protein that can enhance glucuronide uptake but does not transport glucuronide. We have found no indications that GusC acts as a binding protein or interacts directly with GusB, with permeabilized cells, subcellular vesicles, or the purified proteins; there is a significant level of sequence homology of GusC (22.4% amino acid identity with a global alignment) to a porin-like protein of Pseudomonas aeruginosa (27) (accession number AAG03552.1). This may indicate that it acts to facilitate transfer of higher-molecular-weight glucuronides across the outer membrane of E. coli.…”
Section: Resultsmentioning
confidence: 84%
“…By contrast, the product of the gusC gene is an outer membrane protein that can enhance glucuronide uptake but does not transport glucuronide. We have found no indications that GusC acts as a binding protein or interacts directly with GusB, with permeabilized cells, subcellular vesicles, or the purified proteins; there is a significant level of sequence homology of GusC (22.4% amino acid identity with a global alignment) to a porin-like protein of Pseudomonas aeruginosa (27) (accession number AAG03552.1). This may indicate that it acts to facilitate transfer of higher-molecular-weight glucuronides across the outer membrane of E. coli.…”
Section: Resultsmentioning
confidence: 84%
“…One turned out to be the oprD structural gene, and the other region (the opdE gene) might encode a protein influencing the expression of OprD (14). In keeping with this hypothesis, the cloned oprD gene in E. coli was expressed poorly from its own promoter (14) and the level of OprD observed in the outer membrane of P. aeruginosa was influenced by both the growth medium and the carbon source (13). All of the OprD-defective mutants of P. aeruginosa studied to date were genetically undefined, and many were from clinical sources.…”
Section: Resultsmentioning
confidence: 99%
“…It is not possible to directly compare these literature studies with the investigation reported here, since these clinical strains had different genetic backgrounds and since different techniques and media were used. Also, it is known that there are at least one regulatory locus (opdE) (14) and one poorly understood multiple-antibiotic resistance locus (nfxC) (10) that can influence oprD expression and imipenem susceptibility. Furthermore, the potential for obtaining double mutants when utilizing clinical strains or when selecting directly with antibiotics has been described previously (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations